The Role of Scouting Education in Building the Character of Elementary School Students: A Scout Leader's Perspective - Mawardini, Annissa; Amalia, Rachmah; Syafawani, Ummi Rasyida; Zahra, Aurellia Septiara Az (LJPI UI Bunga Bangsa Cirebon, 2025)
Objective: This research aims to discover the Scout Leaders' perspective on the role of Scouting Education in building the character of Elementary School students. Novelty: The study provides insights into the unique challenges and strategies employed by Scout Leaders in character education. Methods: The study employed a qualitative approach utilizing the phenomenological method. Data was collected through in-depth interviews with Scout Leaders at SDIT Amaliah and analyzed following the Miles and Huberman model. Results: The research results have four main focuses: urgency, implementation, challenges, and strategies of Scout Leaders in building student character through Scouting Education. Conclusion: The research concluded that Scouting Education has a significant role in shaping student character, especially the characters of independence, discipline, leadership, caring, courage, responsibility, and cooperation through Scouting activities that have been implemented. Although Scout Leaders face challenges in building student character through Scouting Education, the leaders have a strategy so that character values are still internalized effectively, namely by conducting Scouting activities through fun team games. This research contributes to supporting character building through Scouting Education in Elementary Schools.